(untitled) (Altre Modernità, 2023)
At the beginning of the 20th century, Abruzzo was the destination of two parallel, but completely different journeys: one was undertaken by Anne MacDonell, an English writer and translator of considerable talent, the other involved Carlo Placci, an eminent intellectual and journalist. Both left written memories of their experiences: MacDonell in a detailed periegetic account published as an illustrated volume in 1908, Placci in a much shorter story that first appeared in «Il Marzocco» on 8th July, 1906 and was then included in the collection In Automobile (1908). Starting from the similarities between the two authors – time frame, places described, context and cultural references of the two writers – the contribution intends to offer a reflection on how the differences between MacDonell and Placci influenced their respective narratives.